Europa Modifies Jupiter's Plasma Sheet - J. R. Szalay; J. Saur; D. J. McComas; F. Allegrini; F. Bagenal; S. J. Bolton; R. W. Ebert; T. K. Kim; G. Livadiotis; A. R. Poppe; P. Valek; R. J. Wilson; et al. (Geophysical Research Letters)
Abstract Jupiter's plasma sheet has been understood to be primarily composed of Io‐genic sulfur and oxygen, along with protons at lower mass density. These ions move radially away from Jupiter, filling its magnetosphere. The material in the plasma sheet interacts with Europa, which is also a source of magnetospheric pickup ions, primarily hydrogen and oxygen. Juno's thermal plasma instrument JADE, the Jovian Auroral Distributions Experiment, has provided comprehensive in situ observations of the composition of Jupiter's plasma sheet ions with its Time‐of‐Flight mass‐spectrometry capabilities. Here, we present observations of the magnetospheric composition in the Europa‐Ganymede region of Jupiter's magnetosphere. We find material from Europa is intermittently present at comparable densities to Io‐genic plasma. The intermittency of Europa‐genic signatures suggests Europa's neutral oxygen toroidal cloud is more localized to Europa's vicinity than its hydrogen cloud. These observations reveal a more complex and compositionally diverse magnetosphere than previously thought.